Transcriptional response of salinity stress in red claw crab Uca arcuata - Wang, Bing; Sun, Shaolei; Zhang, Feijun; Han, Zhiqiang (Frontiers in Marine Science, 2025)
This research identified functional genes and regulatory pathways of salinity stress in red claw crab Uca arcuata, which a globally distributed intertidal species inhabiting saline ecosystems, providing data and theoretical basis for the protection and utilization of U. arcuata in global climate change. In this study, we performed RNA sequencing on U. arcuata gill tissues exposed to salinity gradients (15‰, 25‰ control, and 35‰) to profile transcriptional responses. A total of 63.83 GB of high-quality clean reads were generated, yielding 125,462 unigenes with robust assembly metrics (N50 = 969 bp; mean length = 688 bp). The transcriptome analysis predicted 101,280 coding sequences (CDSs) and 52,706 simple sequence repeats (SSRs). Compared with the control group, the high-salinity group obtained 52 differentially expressed genes (DEGs), with 36 upregulated and 16 downregulated genes. The low-salinity group obtained 1,035 DEGs, with 780 upregulated and 255 downregulated genes. GO analysis showed a significant enrichment of DEGs in signal transduction, enzymatic activity, and binding. KEGG analysis showed that most DEGs were associated with signaling pathways and metabolism. APOA1, APOA2, GPX and GST were specific genes related to salinity adaptation. Five DEGs were randomly selected for quantitative RT-PCR validation, and the results demonstrated that the transcriptome data are highly reliable. However, we did not delve into the key functional genes and their regulatory mechanisms. Joint analysis of the genome and transcriptome of U. arcuata should conduct in the future, and comprehensively elucidate its adaptation mechanism to salinity fluctuations.